Symbolic Interactionist Takes on Music. - Denzin, Norman K. (Studies in symbolic interaction., 2016)
Participants from Couch-Stone Symposium 2014 have contributed to this volume on three themes; reflecting a natural progression in scope of symbolic interactionist work in music: moving from observations of the individual to observation of organizations and interdisciplinary observations of music from scholars in related disciplines.